Studi Pelaksanaan Keselamatan Dan Kesehatan Kerja (K3) Pada Laboratorium Jurusan Fisika Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang - Nurun Nayiroh (Jurnal Teknologi dan Manajemen Pengelolaan Laboratorium, 2019)
This study aims to find out 1) the implementation of Occupational Safety and Health (K3); 2) obstacles in implementation (K3); and 3) efforts that can be made to overcome obstacles in the implementation of K3 in the laboratory department of Physics UIN Maulana Malik Ibrahim Malang. This research is a qualitative descriptive study. Data collection techniques include, interviews, observation, and documentation. The subjects in this study were students, lecturers, and the Head of the Laboratory, by determining samples using snowball sampling techniques. The data validity technique used is source triangulation. The results of the study: 1) occupational safety and health in the Physics study program laboratory have been carried out, but conditions are still found where the K3 indicators do not meet the requirements and need to be improved. 2) Obstacle to the implementation of K3 from human factors, namely; there are still users who do not comply with the rules and SOP. Then seen from environmental factors, namely; handling old damaged equipment, inadequate K3 facilities and infrastructure, improper electrical arrangement, and some laboratories without ventilation. Efforts made by the Physics study program laboratory manager to overcome obstacles in the implementation of K3, namely; make alternative replacements for damaged equipment with their own assemblies, borrow cleaning equipment to cleaners to clean the laboratory, make writings on K3 appeals posted on the walls as K3 signs, electrical plugs on the floor covered with black plaster and given signs, made artificial ventilation and added a blower, gave an appeal at the beginning of each practicum meeting (briefing practicum) and supervision by assistants and laboratory assistants during the practicum, and put up posters of appeals about the use of tools in accordance with the SOP posted on the laboratory wall.